Sensitivity of an international notification system for wildlife diseases: A case study using the OIE‐WAHIS data on tularemia. (29th January 2022) - Fanelli, Angela; Awada, Lina; Caceres‐Soto, Paula; Diaz, François; Grillo, Tiggy; Gizo, Itlala; Hamilton, Keith; Rolez, Christine Leon; Melens, Peter; Morales, Roberta; Mur, Lina; Muset, Sophie; et al.
Abstract: The World Organization for Animal Health (OIE) has recently developed a Wildlife Health Framework to respond to the need of members to manage the risk from emerging diseases at the animal–human–ecosystem interface. One of its objectives is to improve surveillance systems, early detection and notification of wildlife diseases. Members share information on disease occurrence by reporting through the OIE World Animal Health Information System (OIE‐WAHIS—formerly known as 'WAHIS'). To evaluate the capacity of a surveillance system to detect disease events, it is important to quantify the gap between all known events and those officially notified to the OIE. This study used capture–recapture analysis to estimate the sensitivity of the OIE‐WAHIS system for a OIE‐listed wildlife disease by comparing information from publicly available sources to identify undetected events. This article presents a case study of the occurrence of tularemia in lagomorphs among selected North American and European countries during the period 2014–2019. First, an analysis using three data sources (OIE‐WAHIS, ProMED, WHO‐EIOS [Epidemic Intelligence from Open Sources]) was conducted. Subsequent analysis then explored the model integrating information from a fourth source (scientific literature collected in PubMed). Two models were built to evaluate both the sensitivity of the OIE‐WAHIS using media reports (ProMED and WHO‐EIOS), which is likely to represent current closer to real‐time events, and published scientific data, which is more useful for retrospective analysis. Using the three‐source approach, the predicted number of tularemia events was 93 (95% CI: 75–114), with an OIE‐WAHIS sensitivity of 90%. In the four‐source approach, the number of predicted events increased to 120 (95% CI: 99–143), dropping the sensitivity of the OIE‐WAHIS to 70%. The results indicate a good sensitivity of the OIE‐WAHIS system using the three‐source approach, but lower sensitivity when including information from the scientific literature. Further analysis should be undertaken to identify diseases and regions for which international reporting presents a low sensitivity. This will enable evaluation and prioritization of underreported OIE‐listed wildlife diseases and identify areas of focus as part of the Wildlife Health Framework. This study also highlights the need for stronger collaborations between academia and National Veterinary Services to enhance surveillance systems for notifiable diseases.